Recovery of Li and Co from LiCoO2 via Hydrometallurgical–Electrodialytic Treatment - Cerrillo-González, María del Mar; Villén-Guzmán, María Dolores; Vereda-Alonso, Carlos; Gómez-Lahoz, César; Rodríguez-Maroto, José Miguel; Paz-García, Juan Manuel (MDPI, 2020)
Lithium-ion batteries play an important role in our modern society as the main option to power portable electronic devices and electric vehicles. The growing demand for these batteries encourages the development of more efficient recycling processes, aiming to decrease the environmental impact of the spent batteries and recover their valuable components. In this paper, a combined hydrometallurgical-electrodialytic method is proposed for processing battery waste. In the combined technique, the amount of leaching solution is reduced as acid is generated via electrolysis. At the same time, the use of ion-exchange membranes and the possibility of electroplating allows for a selective separation of the target metals. Experiments were performed using LiCoO2, which is one of the most used cathodes in lithium-ion batteries. First, 0.1 M HCl solution was used in batch extractions to study the kinetics of LiCoO2 dissolution, reaching an extraction of 30% and 69% of cobalt and lithium, respectively. Secondly, hydrometallurgical extraction experiments were carried out in three-compartment electrodialytic cells, enhanced with cation-exchange membranes. Experiments yielded to a selective recovery in the catholyte of 62% of lithium and 33% of cobalt, 80% of the latter electrodeposited at the cathode.
Keywords: Cobalto - Aleaciones; Litio - Aleaciones; Pilas de litio; Litio - Reciclado; Óxido de litio-cobalto - Reciclado; LiCoO2; Critical Raw Materials; Lithium-ion battery recycling; Electrodialysis